Compare Mean Central Corneal Thickness with Ultrasound Pachymetry and Spectral-Domain Optical Coherence Tomography in Patients Presenting with Glaucoma - Sohaib Afzal, Shujah Ur Rehman, Muhammad Mafzaal Jafar, Usama Javaid, Aqsa Akram (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The optic nerve damage with the ultimate loss of vision resulting from a clutch of diseases named Glaucoma. In many conditions including, corneal dystrophies, corneal edema, and endothelial diseases of the cornea, the important biometric is Central corneal thickness (CCT). Objective: To find the difference in mean CCT with spectral-domain optical coherence tomography and ultrasound pachymetry in patients presenting with Glaucoma. Material & Methods: The study design opted was the observational cross-section. The study was done in tertiary care hospital. A total of 180 patients were registered for the present study. Both techniques noted the CCT value of all patients. Once the data was collected, it was stored electronically and analyzed by using SPSS version 20.0. Results: 40.00±11.50 years was the average age of all the patients. There were 89(49.44%) males and 91(50.56%) females. The mean CCT was 531.01±28.54µm on OCT and 530.01±29.74µm on USP. The mean difference in CCT was 3.93±3.13µm between OCT & USP. The difference was statistically insignificant (p<0.05). Conclusion: There is a statistically insignificant difference between the mean CCT with USP and spectral domain OCT patients presenting with Glaucoma. Keywords: Glaucoma, Optical Coherence Tomography, Central Corneal Thickness.